Preparation of a Low-Calorie, Gluten-Free All-in-One Cake Mix, Containing Bacillus Coagulans Using Quinoa and Inulin Functionality - Khatereh Amini; Anousheh Sharifan; Babak Ghiassi Tarzi; Reza Azizinezhad (Journal of Food Quality)
Celiac patients must follow a strict gluten-free diet along the life that leads to many nutritional deficiencies. This study aimed to produce an “all-in-one gluten-free cakemix based on quinoa flour” for celiac patients and other gluten-sensitive people. Nine treatments were provided with quinoa flour (25, 27.5, and 30% of total formula), inulin as a prebiotic, fat replacer and natural sweetener (2.4, 3.2, and 4% of total formula). The content of oil was reduced using oil powder consisting of sunflower oil and wall materials (resistant starch and maltodextrin 50 : 50). Bacillus coagulans was added as a probiotic bacteria. A commercial cakemix was considered as a control sample. The nutritional and chemical properties of cake mixes (percentage of moisture, protein, mineral, carbohydrate, crude fiber, fat, and calorie) and physical and textural properties of cakes (springiness, specific volume, porosity, chewiness, browning reaction, moisture, and water activity) were tested. Data were analyzed by https://graphpad.ir/prism/software using one way analysis of variance (ANOVA). After sensory evaluation, the treatment number 5 was selected as the most acceptable cake among all treatments. Its amino acid profile, fatty acid profile, and peroxide index were determined. The minerals, protein, and fiber of quinoa cake mixes were significantly higher, and the fat, carbohydrate and calorie were lower than control. Addition of quinoa reduced springiness, specific volume, porosity, chewiness, and increased the browning reaction. But these changes did not have a very negative effect in general. The moisture, water activity, and bacteria count changes were followed during four days of cakes preservation in refrigerator. The reduction trend of quinoa cakes moisture and water activity was slower than control. The number of bacteria was enough to be considered as a probiotic product after 4 days. Quinoa flour could improve the nutritional and functional properties of gluten-free cake mixes.